PENGARUH DIGITAL MARKETING DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN RINVITATION.ID - Hasna Aufa Kamila; Deni Solihin (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the influence of digital marketing and service quality on customer satisfaction at Rinvitation.id. The research uses a quantitative approach with survey methods and data analysis using SPSS. The population in this study were customers of Rinvitation.id, with a total sample of 100 respondents. The data were tested using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination (R²). The results showed that digital marketing (X1) and service quality (X2) had a significant effect both partially and simultaneously on customer satisfaction (Y). The contribution of the two independent variables to customer satisfaction was 62.3%, while the remaining 37.7% was influenced by other factors not examined. Thus, digital marketing and service quality are proven to play an important role in increasing customer satisfaction at Rinvitation.id.